Initial Clinical Presentation of Systematic Lupus Erythematosus (SLE) Patientsin Cipto Mangunkusumo Hospital - Teresa Isabela (Indonesian Journal of Rheumatology, 2024)
Background. Systemic Lupus Erythematosus (SLE) is a systemicautoimmune disease characterized by highly diverse and nonspecificsymptoms with clinical presentations involving more than one organ systemwhich often leads to delayed diagnosis and poor prognosis. This study aimsto understand patients’ initial clinical presentation in order to enhance earlydetection and establish an early diagnosis. Methods. This descriptive crosssectionalquantitativestudy included patients who commenced their visitsto the Rheumatology Clinic at RSCM from May 2021-December 2022. Aconsecutive sampling method was used, and data were analyzed for age,gender, symptom onset, as well as patients' initial clinical presentations(SPSS 25.0). Results. Out of 231 subjects, 96.1% were females. A total of38.1% of the patients belonged to the 21-30 age group, and symptom onsetwas most commonly observed in the 0-1 year age group, accounting for67.5%. Approximately 24.2% of the patients exhibited constitutionalmanifestations with involvement of other organs, including musculoskeletal(87.4%), mucocutaneous (84%), hematologic (3.,5%), renal (33.3%), andneuropsychiatric (8.7%) systems. Lungs, heart, blood vessels, gastrointestinal and hepatic systems, eyes, obstetric, and endocrineinvolvements were not found in this study. Among the 231 subjects, 44.2%of them had simultaneous involvement of two organs, which emerged as theirinitial clinical presentation. Conclusion. Musculoskeletal andmucocutaneous involvement were most commonly observed as th e initialclinical presentation of SLE patients at RSCM, followed by hematologic,renal, and neuropsychiatric involvement.